2022
DOI: 10.1007/s00343-021-1092-z
|View full text |Cite
|
Sign up to set email alerts
|

Two bicistronic DNA vaccines against Vibrio anguillarum and the immune effects on flounder Paralichthys olivaceus

Abstract: Chemokines are cytokines that can promote the activation and migration of immune cells, and increase the recognition of antigen by antigen-presenting cells (APC). Previous studies showed that a DNA vaccine can induce humoral and cellular immune responses of fl ounder after immunization. To explore the improvement of chemokines on the effi ciency of OmpK vaccine, two bicistronic DNA candidate vaccines were constructed and the immune responses they induced in the fl ounder were investigated by reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…To enhance the protective effect of OmpK as a DNA vaccine candidate, adjuvants were co-administered with the vaccine. The previous study has shown that two chemokines, CCL4 and CCL19, were inserted into the OmpK-based DNA vaccine ( 39 ) and provided RPS of 74.1% and 63.3%, respectively. Furthermore, the leukocytes were recruited to the injection site after immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the protective effect of OmpK as a DNA vaccine candidate, adjuvants were co-administered with the vaccine. The previous study has shown that two chemokines, CCL4 and CCL19, were inserted into the OmpK-based DNA vaccine ( 39 ) and provided RPS of 74.1% and 63.3%, respectively. Furthermore, the leukocytes were recruited to the injection site after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit against OmpK antibodies were produced by Li et al. ( 39 ). The secondary antibodies included Dylight 488 (Abbkine; diluted 1:1,000) Rabbit or mouse IgG, Dylight 649 (Abbkine; diluted 1:1,000) Rabbit or mouse IgG, alkaline phosphatase (AP)-conjugated goat anti-rabbit IgG (H + L) (Abbkine; diluted 1:5,000), and HRP-conjugated goat anti-mouse IgG (Abbkine; diluted 1:5,000).…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli ( E. coli ) , Staphylococcus aureus ( S. aureus ), Edwardsiella tarda ( E. tarda ), Vibrio anguillarum ( V. anguillarum ), and hirame rhabdovirus (HIRRV) strain were previously isolated from diseased flounder and stored in our laborotory ( 23 , 24 ). Bacteria were cultured in Luria-Bertani (LB) medium up to an OD600 of 0.5 and harvested by centrifugation before use.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that a DNA vaccine based on the zinc metalloprotease EmpA already displayed gratifying results against V. anguillarum early in 2009 [ 65 ]. In recent years, several DNA and subunit vaccines based on V. anguillarum outer membrane proteins and their recombinant proteins have shown effective and long-lasting immunity [ 66 , 67 , 68 , 69 ]. It has also been proven in the study that particularly high protection against V. anguillarum infection exists when related proteins are formulated as bivalent vaccines [ 68 ].…”
Section: Control and Prevention Strategies Of Vibriosmentioning
confidence: 99%